Considering malocclusion as a disability - Blanch Keely; Antoun Joe; Smith Lee; Jack Hannah; Fowler Peter; Page Lyndie Foster (Sciendo, 2019)
Numerous studies have indicated that a malocclusion possibly affects young people's well-being and oral health-related quality of life (OHRQoL). Dento-facial aesthetics may influence how people are judged and may elicit social consequences such as bullying and negative comments. The present study aimed to explore the impact of a malocclusion on young New Zealanders who sought subsidised treatment from the Wish for a Smile (WFAS) organisation and to determine their motivation for seeking care.